Introduction: Transport and land use in childhood - Ron Buliung; Raktim Mitra (Journal of Transport and Land Use)
What is the relationship between childhood, transportation, and land use? What are the social and environmental—along with political, economic, and policy-related factors and forces—that produce transport in childhood? How do we create places where childhood is considered more explicitly in transport and land-use planning? What is the effect of research methods in producing knowledge about the relationship between childhood, transport, and land use? These are some of questions that shaped the call for papers, “Children and Youth Transport and Land Use: Theory, Method and Applications,” for the 2014 World Symposium on Transportation and Land Use Research held in Delft, Netherlands.